Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Solving literal equations
Solving for y
-x + 3y = -6


Sagot :

Since y is the variable, x is considered here as a constant.

Then :

-x + 3y = -6

we add x in both left side and right side of the equation :

-x + x + 3y = -6 + x

3y = -6 + x

Then we divide both side by three :

3y / 3 = (-6+x) /3

y = (-6+x)/3

y = -6/3 + x/3

y= -2 + x/3